Ureteral Stricture after Laparoscopic Tubal Ligation due to Suturing of the Serosa - Berat Cem Özgür; Ahmet Metin Hasçiçek; Tolga Karakan; Cem Nedim Yücetürk; Erim Ersoy (Case Reports in Urology)
Strictures secondary to traumas of the ureter are some of the complications of urogynecologic surgery. We present a 43-year-old female who had a history of laparoscopic tubal ligation a year ago and was admitted to our department with recurrent flank and inguinal pain. It was soon understood that a suture has pulled the ureter from the lateral serosa of the upper part to the lateral serosa of the lower part causing dilatation of the proximal and midureter because of the previous surgery while there was no damage on the ureteral lumen. Consequently successful reconstruction was performed with open ureteroureterostomy.